Beneficial effects and mechanism of lead ions for bastnaesite flotation with octyl hydroxamic acid collector. (15th March 2020) - Lin, Yiming; Chen, Cheng; Wang, Weiqing; Jiang, Ying; Cao, Xuan
Graphical abstract: Highlights: The presence of Pb 2+ greatly enhances the floatability of bastnaesite with OHA collector. Pb(OH) + and Pb 2+ were adsorbed onto bastnaesite surface and increase the activated sites. The active Pb sites chemically interacted with OHA on bastnaesite surface. The adsorbed lead species on the bastnaesite surface increase the adsorption of OHA. Abstract: The beneficial effects and mechanism of Pb ions (Pb 2+ ) for bastnaesite flotation were systematically investigated. The results of micro-flotation tests indicated that the Pb 2+ effectively enhanced the floatability of bastnaesite with octyl hydroxamic acid (OHA) collector. Maximum recovery of 67% was obtained at pH 8–9. Adsorption of the hydrolyzing species of Pb occurred at this pH, which provided more active sites on the bastnaesite surface for OHA absorption. Furthermore, lead species interacted with active Ce sites to form lead-containing complexes (Ce-O-Pb) on the bastnaesite surface, and the hydrophobic Pb-OHA chelates were formed via chemical adsorption between Pb 2+ -activated bastnaesite and OHA. These findings were confirmed by adsorption measurements, zeta-potential measurements, Fourier transform infrared analysis (FT-IR), and X-ray photoelectron spectroscopy (XPS).